An Overview of Acoustic-Based Interventions to Improve Motor Symptoms in Parkinson’s Disease - Leuk, Jessie Siew Pin; Low, Linette Li Neng; Teo, Wei-Peng (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease (PD) is characterized by motor and cognitive deficits that negatively impact on activities of daily living. While dopaminergic medications are used to attenuate motor symptoms, adjuvant therapies such as acoustic-based non-pharmacological interventions are used as a complement to standard drug treatments. At present, preliminary studies of acoustic-based interventions such as rhythmic-auditory stimulation (RAS) and vibroacoustic therapy (VAT) suggest two competing hypotheses; 1) RAS may recruit alternative motor networks that may bypass faulty spatiotemporal motor networks of movement in PD; or 2) the use of RAS enhances BG function through entrainment of beta oscillatory activities. In this review, we discuss the mechanisms underlying the role of acoustic-based interventions and how it may serve to improve motor deficits such as gait impairments and tremors. We further provide suggestions for future work that may use a combination of RAS, VAT and physical therapy to improve motor function in PD.